Occurrence of Irreducible Water and Its Influences on Gas-Bearing Property of Gas Shales From Shallow Longmaxi Formation in the Xishui Area, Guizhou, Southern China - Sun, Jian; Xiao, Xianming; Wei, Qiang; Cheng, Peng; Tian, Hui (Frontiers in Earth Science, 2021)
Systematic studies are quite rare on the gas-bearing property and its controlling factors of the shallow Longmaxi shale outside the Sichuan Basin. In a previous study, the gas in place contents of a suit of Longmaxi shale samples with a depth range of 362–394 m from the well XK2, which was drilled in the Xishui area, Guizhou, southern China, were reported. In the present study, the pore structure parameters and irreducible water occurrence characteristics of those samples, and their influences on the gas-bearing property were further investigated. The results show that, compared to the dry sample, the non-micropore specific surface areas and micropore volumes of the moist sample are significantly reduced by an average value of 61 and 30%, respectively, and that the water averagely occupies 82 and 41% of the inorganic and organic non-micropore specific surface areas, respectively, and 44 and 18% of the inorganic and organic micropore volumes, respectively. The shallow shale reservoir is dominated by adsorbed gas. It accounts for 66–93% of the total gas. The water significantly decreases the adsorption capacity of the inorganic matte (mainly clay minerals) pores, but has a limited influence on that of the organic matter pores. The adsorbed gas occurs mostly in the organic matter nanopores, and even if the shales were highly saturated with the water, they can still store a certain amount of the adsorbed gas. These results are to provide some guides for the evaluation and exploration of the shallow Longmaxi shale located in the strongly tectonic transformation areas of southern China.